Karakterisasi Fisikokimia Beras Galur-galur Padi Hitam Dihaploid - Muhammad Jauhar Firdaus; Bambang Sapta Purwoko; Iswari Saraswati Dewi; Willy Bayuardi Suwarno (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2022)
The quality of grain and rice which includes physical and chemical quality (physicochemical) is a consumer preference that needs to be considered. The character of the quality of grain and rice includes appearance, texture and taste. The aim of the study was to measure or identify quantitatively the physicochemical character of the dihaploid rice lines of black rice. The experiment was conducted at the Quality Laboratory, Muara Experimental Station, Indonesian Center for Rice Research (BB Padi) from August to September 2021. The study used a completely randomized design with 10 replicates or samples per genotype. The genotypes used consisted of 16 (14 dihaploid lines of black rice and two check varieties, namely Aek Sibundong and Jeliteng). Observations of physical quality included water content, broken husk rice, head rice, milled rice, rice shape, length of rice and grains of rice lime. The chemical characters of rice observed were amylose content, gelatinization temperature and organoleptic. The results showed that the AW6 line had a close similarity with the check variety shown in the cluster analysis in Group 1. The distinguishing traits in Group 1 were 13.6% moisture content, 88.7% head rice, 76% broken rice, 70% milled rice, score alkaline 1-4, medium to high gelatinization temperature, lean shape, savory taste and small liming. The AW6 line was included in Group 1 because it had similar characteristics to the check varieties. Keywords: amylose, black rice, physicochemical